If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4t-1=6t+2
We move all terms to the left:
4t-1-(6t+2)=0
We get rid of parentheses
4t-6t-2-1=0
We add all the numbers together, and all the variables
-2t-3=0
We move all terms containing t to the left, all other terms to the right
-2t=3
t=3/-2
t=-1+1/2
| (-5x-9)+6=-4(x-9) | | 6d=36+15d | | Y=9-5x-2 | | 49-5(1-n)=3(4-2n)-2 | | (x-17)=(5x-1) | | 2y/3-3/4=1/2 | | (5x+28)=(7x-4)=180 | | 5x+16=2(2x+1) | | 7.6x=53.2 | | 4y-24=5y-10 | | 1/2(-4K+26)=3+11k | | (7x-9)=(4x-3) | | x+8/18=1/9+x-6/5 | | x/(x-2)+2/3=2/(x-2) | | 4(3)+3y=9 | | w(w-6)^2=0 | | 4(2+v)+3v=13v | | -7=74z÷2+1 | | -7=3-(5-a) | | 8=4z÷2 | | 32x=33 | | 2x-6=6x-30 | | -7=4z÷2+1 | | 2x+1/3x=8 | | 6/5y-1=41 | | 10x+80=80 | | (1/6)2m=36 | | 30000=826x=15463 | | 15x+25=-25 | | 1/3(x+1)-2x=1/6 | | 25=826x+15463 | | (x+27)=(2x-7) |